Environmental tolerance of the free-living stages of the poultry roundworm (Ascaridia galli) - Tarbiat, Behdad (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2012)
As the EU ban on conventional cages (1999 EU-directive) drew closer, most European countries moved towards alternative systems. Consequently, barn and free-range systems has become increasingly popular. Regardless of how welfare has improved, this major change in husbandry likely affects the parasite transportation. Accordingly, recent reports have unanimously shown that prevalence of round worm infection, in particular Ascaridia galli has increased dramatically. Although management practices have shown to be somehow efficient with regard to parasite control in caged system, at this time there is no effective way to prevent and eliminate the existing parasite in non-caged system. For better understanding the infection dynamics of A. galli a series of experiments was carried out to study the environmental factors (temperature, relative humidity, pH and oxygen) influencing the fate of A. galli eggs within the environment. In addition, two more experiments were run to evaluate the efficacy of thiabendazole and commercial broad spectrum disinfectant Chlorocresol (Interkokask). Survivability of the eggs with regard to the age of the parasite eggs was investigated as well.